Mechanism Design with Narratives - Matthias Lang (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Individuals use narratives as rationales or justifications to make their claims more convincing. I provide a general framework for partial verifiability based on narratives. Narratives give many reasons and arguments. The receiver derives the message's meaning by aggregating these reasons; her private information tells her whether some potential reasons support the sender's claims. Therefore, the receiver detects misreports with positive probability. Narratives flexibly allow for different degrees of partial verifiability and allow using the revelation principle. Considering mechanism design as an example, I prove that narratives are so powerful to implement efficient trade in the canonical bilateral-trade setting.
Keywords: D81; D82; D86; 330; narrative; communication; partial verifiability; mechanism design; bilateral trade